First make it a "Y=" equation.
Y = x2-5x+6
Switch the Y with the x's
X = Y2-5Y+6
Solve for X
X-6 = Y2-5Y
X-6/5 = Y2
Square root of ((x-6)/5)) = Y
Kind of confusing, but I hope this helps!
You don't. That is not a "one to one" function and so does not have an inverse. If is the inverse of f(x), then we must have , that is, must 'undo' whatever f does. But f(6)= 0 and f(-1)= 0. can't be both 6 and -1!
Luke774, for some reason, chose to take only the "+" sign on the square root. That's valid but gives the inverse of a slightly different function: with and undefined for x< 5/2. Same formula but different domain so different function.